Methodological Approaches to Assessing Social and Economic Differentiation of Economic Space - Vyacheslav K. Melkov; Elena A. Zhidkova (Вестник Кемеровского государственного университета. Серия: политические, социологические и экономические науки)
This article introduces a system of contemporary methodological approaches to assessing the socio-economic differentiation of the economic space in the Russian Federation. Each approach is a set of indicators that can be applied to Russia’s socio-economic system for assessment and analysis of its territorial differentiation. The research methodology included a review, content analysis, dialectical, approach, and systemic approach, as well as the methods of economic statistics, graphical representation, and econometric analysis. The resulting scheme of Logical stages of assessing socio-economic territorial differentiation made it possible to identify the key factors behind the interregional differences. A case study shows how the choice of appropriate indicators and may affect the results and conclusions of a territorial differentiation assessment. Well-chosen analytical tools provide effective regional policies. Russia’s socio-economic heterogeneity needs a comprehensive approach, especially in the context of the current economic and social challenges to the domestic territorial spatial development.